Palmitoylethanolamide causes dose-dependent changes in brain function and the lipidome - Balaji, Shreyas; Woodward, Taylor J.; Richter, Emily; Chang, Arnold; Otiz, Richard; Kulkarni, Praveen P.; Balaji, Kaashyap; Bradshaw, Heather B.; Ferris, Craig F. (Frontiers in Neuroscience, 2024)
The present studies were undertaken to understand the effects of the commonly used nutraceutical PEA on brain function and lipid chemistry. These studies using MRI and broad-scale lipidomics are without precedent in animal or human research. During the MRI scanning session awake rats were given one of three doses of PEA (3, 10, or 30 mg/kg) or vehicle and imaged for changes in BOLD signal and functional connectivity. There was an inverse dose–response for negative BOLD suggesting a decrease in brain activity affecting the prefrontal ctx, sensorimotor cortices, basal ganglia and thalamus. However, there was a dose-dependent increase in functional connectivity in these same brain areas. Plasma and CNS levels of PEA and over 80 endogenous lipids (endolipids) were determined post treatment. While levels of PEA in the CNS were significantly higher after 30 mg/kg treatment, levels of the endocannabinoid, Anandamide, and at least 20 additional endolipids, were significantly lower across the CNS. Of the 78 endolipids that were detected in all CNS regions evaluated, 51 of them were modulated in at least one of the regions. Taken together, the functional connectivity and lipidomics changes provide evidence that PEA treatment drives substantial changes in CNS activity.